Budaya Patriarki Akar KDRT Terhadap PerempuanBudaya Patriarki : Pengaruhnya Terhadap Kekerasan Dalam Rumah Tangga Terhadap Perempuan (Di Bidang Ekonomi) - Nadia Eka Putri; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This article analyzes the influence of patriarchal culture on domestic violence (KDRT) against women in Indonesia, particularly in the economic context. The study argues that patriarchal culture creates gender inequality that disadvantages women, limiting their access to education, employment, and economic resources, making them vulnerable to exploitation and violence. Women’s economic dependence on men, coupled with social norms that demand women’s obedience and acceptance of mistreatment, creates a vicious cycle that is difficult to break. The article also discusses the economic impact of KDRT on women, as well as the difficulties in accessing justice for victims of KDRT, which are influenced by patriarchal culture.